Tendência da fecundidade em Moçambique (1987-2007): nível, padrão etário, parturição progressiva e intervalo entre nascimentos - Francisco Alberto Macaringue (2015)
Understanding the evolution of fertility plays an important role in demographic dynamics. Fertility changes have a direct impact on population growth, especially for countries with high growth rates. However, data quality is important, especially for developing countries, as is the case in Mozambique, where vital statistics are still unreliable and censuses and household surveys are the main source of information. This work aims to contribute to a better perception of the most recent level of fertility, to analyze it evolution between 19872007. Data from the 1997 and 2007 Demographic Census, made available by IPUMS, and the reconstructed birth stories from the two census editions are used. The reconstruction of birth histories used household members data and a methodology that uses a pairing process to input missing data. The work combines several indirect methods, which aim to estimate and correct the results. For the analysis of trends, we present historical series of: Total fertility rate (TFR), Age specific rates, parity progression ratios and birth Intervals. The Own Child Method was used to validate the trend of the TFR historical series and the Brass P/F Method was used to correct the TFR level. The results are presented according to four agglomerates: Mozambique, Metropolitan Maputo, Urban Rest and Rural; and two educational categories: incomplete primary education and complete primary education. The results point to a slight decline in fertility in the country from 1997 to 2007. However, women in metropolitan Maputo and with complete primary education would have a more pronounced fall in fertility. The decline observed in this region had its beginning in the 1980s. Using the parity progression ratios the results suggest a decline in higher order parity in older cohorts. The birth intervals are wider among women with complete primary education, residing in Metropolitan Maputo and in the urban rest. We believe that fertility decline in these two regions can boost fertility decline in Mozambique.